2019
DOI: 10.3390/su11195243
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Water Balance of Selected Field Crops in Different Agricultural Regions of the Czech Republic Using Fao-56 and Soil Hydrological Approaches

Abstract: Long-term water balance (WB) of four selected crops (winter wheat, oilseed rape, silage maize, semi-early potatoes) was determined at the field block scale in the Czech Republic for all agricultural growing areas (AGAs): maize-, beet-, potato- and mountain-AGAs for the 1981–2010 period. A novel approach for the calculation of WB was employed, which combined the FAO-56 method for crop water requirements (CWRs) with sources of available water from precipitation, soil, and groundwater. The computed WB was divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…The Czech Republic is not generally considered as a drought-prone region in Europe, but there are more and more droughts were recorded, for example, 2000, 2001, 2003, 2014, 2015, and 2018. It was reported that the highest water deficit was recorded for maize growing areas from the field block scale in the Czech Republic due to low precipitation and high water requirements, and about 39.6% (9745.5 km 2 ) of silage maize growing area was effected 25 . The droughts had a profound effect on national and regional agricultural production in the Czech Republic, with yields being consistently lower than in normal years 26 .…”
Section: Resultsmentioning
confidence: 99%
“…The Czech Republic is not generally considered as a drought-prone region in Europe, but there are more and more droughts were recorded, for example, 2000, 2001, 2003, 2014, 2015, and 2018. It was reported that the highest water deficit was recorded for maize growing areas from the field block scale in the Czech Republic due to low precipitation and high water requirements, and about 39.6% (9745.5 km 2 ) of silage maize growing area was effected 25 . The droughts had a profound effect on national and regional agricultural production in the Czech Republic, with yields being consistently lower than in normal years 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Since crop canopy water content is conditional to the amount water getting in root zone from rainfall (Imran et al, 2015), it can be considered as independent variable in modeling simulation to the dependent variable of crop land zonal statistics (Hunt, Jr. et al, 2009). With this principle, it can be possible to predicate crop canopy water and to observe crop root zone soil water content (Duffková et al, 2019;Manual, 2002;Tadesse et al, 2015). As the result, crop land zonal statistics which has used to join crop land shape file of classified crop land.The wet season crop land zonal biomass statistics of main crops in the study area (Fig 7) is under acceptable range for crop coefficient [Kc] for all crop growth curve for rainy season uncertainty interval (start/maximum/end) (0.25 ≤ /Crop zonal EVI≤ 0.75) (FAO ASIS, 2022).…”
Section: Crop Land Evimentioning
confidence: 99%
“…On one hand, there is the professionalism and the certainty of supply from a regional water supply system [37,88], and on the other is the advantage of self-sufficiency and the positive impact of the local community's involvement in the use of local natural resources and their help in protecting them [40,41,57,89]. A key factor in the selection of a proper solution can be the natural conditions of individual municipalities; therefore, on a local level, their detailed analysis and monitoring is recommended as a starting point for adaptation measures for the impacts of climate change [90][91][92].…”
Section: Insufficient Drinking Water Supply As a Limiting Factor To The Socio-economic Development Of Municipalitiesmentioning
confidence: 99%